An Analysis of One-Star Online Reviews and Responses in the Washington, D.C., Lodging Market. (February 2013) - Levy, Stuart E.; Duan, Wenjing; Boo, Soyoung
The hotel industry continues to develop strategies for addressing consumer-generated online reviews, and particularly responding to poor reviews, which can have a damaging effect on a hotel's reputation. To gain a greater understanding of the dynamics of poor reviews, this study analyzed 1, 946 one-star reviews from ten popular online review websites, as well as 225 management responses from eighty-six Washington, D.C., hotels. A comprehensive complaint framework found that the most common complaints related to front desk staff, bathroom issues, room cleanliness, and guestroom noise issues. Complaints were also analyzed by hotel characteristics, including chain-scale segments, and reviewer characteristics, including purpose of travel and geographic location. Examining the reviews, highly rated hotels often respond to online complaints with appreciation, apologies, and explanations for what had gone wrong. Compensation adjustments are rarely mentioned by any hotel. The increasingly prominent role of social media necessitates that hotels use online reviews for market research and service recovery opportunities, regardless of whether they respond publicly.